Em busca do conjunto Paulo Freire: uma construção historiográfica latino-americana das ações do estado, técnicos e população na produção de habitação social (1950-1990) - Lima, Apoenna Caetano (2023)
This study compiles historical contributions on practices linked to the actions of the State, technicians and popular organizations in one historiographic construction - of several possible ones - of the Paulo Freire Complex. The objective of the research is to develop an historical version that complements the predominant panorama identiʉied in the productions that address this collective autoconstruction and self-managed social housing. To this end, a methodological path was structured that is based on the understanding of Michel Foucault's genealogical historiographical approach, as well as that of “assembly” by Paola Berenstein Jacques. The work is divided into two parts. Part I describes the predominant historical perspective, recorded in documents and productions that narrate the events that culminated in the Paulo Freire Complex. Part II presents a more elastic perspective, built based on two trajectories that emerge from the production of the set: the trajectory of formation and that of construction technique. To this end, we use contributions elaborated on Latin American experiences that occurred after the Second World War and are related to the aspects mapped in part I. The route, assembled from these entries, led to clues that connect the object of research to past events that were little related or even named in previous versions of this historiography.